QSAR studies on piperazinylalkyhsoxazole analogues selectively acting on dopaminie D-3 receptor by HQSAR and CoMFA - Cha, MY; Lee, IY; Cha, JH; Choi, KI; Cho, YS; Koh, HY; Pae, AN (PERGAMON-ELSEVIER SCIENCE LTD, 2003)
QSAR studies for piperazinylalkylisoxazole analogues were conducted by hologram QSAR (HQSAR) and comparative molecular field analysis (CoMFA) to explain the binding affinities of 264 ligands acting on dopamine D-3 receptor. The HQSAR was assessed by r(2) value of 0.917 and cross validated q(2) value of 0.841. In the CoMFA, r(2) is 0.919 and cross validated q(2) is 0.727. The results provide the tools for predicting the affinity of related compounds and guiding the design of new ligands. (C) 2003 Elsevier Science Ltd. All rights reserved.